2013
DOI: 10.1194/jlr.m031963
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 deficiency in mice reduces intestinal triglyceride absorption and hepatic triglyceride secretion

Abstract: Obesity is accompanied by low-grade chronic systemic infl ammation characterized by increased circulating levels of proinfl ammatory cytokines, including interleukin (IL)-1 ␤ , tumor necrosis factor (TNF)-␣ , and IL-6 ( 1 ). Activation of infl ammatory pathways induces metabolic disturbances, leading to insulin resistance, dyslipidemia, and cardiovascular diseases. Caspase-1 is a cysteine protease that is known for its crucial role in the activation of the proinfl ammatory cytokines IL-18 and IL-1 ␤ . Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 41 publications
7
44
1
Order By: Relevance
“…When challenged with a bolus of lipid, as might occur after a high-fat meal, caspase-1-deficient mice demonstrated dramatically accelerated clearance of lipid from plasma with no quantitative alteration of lipid production from the gut or liver. Surprisingly, these data contrast with the recently published work by van Diepen et al (37), in which the authors reported reduced TG absorption and reduced hepatic VLDL production. Of note, these authors used Triton, rather than poloxamer, to inhibit LPL and demonstrate altered VLDL production.…”
Section: Discussioncontrasting
confidence: 99%
“…When challenged with a bolus of lipid, as might occur after a high-fat meal, caspase-1-deficient mice demonstrated dramatically accelerated clearance of lipid from plasma with no quantitative alteration of lipid production from the gut or liver. Surprisingly, these data contrast with the recently published work by van Diepen et al (37), in which the authors reported reduced TG absorption and reduced hepatic VLDL production. Of note, these authors used Triton, rather than poloxamer, to inhibit LPL and demonstrate altered VLDL production.…”
Section: Discussioncontrasting
confidence: 99%
“…Intestinal and hepatic gene expression analysis showed that caspase-1 deficiency did not affect fatty acid oxidation or fatty acid uptake but rather reduced intracellular fatty acid transport, thereby limiting lipid availability for the assembly and secretion of triglyceride-rich lipoproteins. 45 These results reveal a novel function for caspase-1 or caspase-1-cleaved substrates in controlling intestinal triglyceride absorption and hepatic triglyceride secretion.…”
Section: Discussionmentioning
confidence: 97%
“…Of note, in a recent publication, caspase-1 deficiency in mice was linked to intestinal lipid malabsorption. 45 In fact, oral gavage of [ 3 H] triglyceride-containing olive oil revealed that caspase-1 deficiency reduced triglyceride absorption and subsequent uptake of triglyceride-derived fatty acid in liver, muscle, and adipose tissue. Similarly, despite an elevated hepatic triglyceride content, caspase-1 deficiency reduced hepatic very-low-density lipoprotein and triglyceride production.…”
Section: Discussionmentioning
confidence: 99%
“…Rat underwent an oral fat tolerance test as previously described [25]. After an overnight fast, blood samples were obtained at 0, 1, 2, 3 and 5 h after the administration of an oral dose of olive oil (5 μL/g of body weight), olive oil and OTP (5 μL/g of body weight and 1 g/kg of body weight, respectively) and olive oil and OTP (5 μL/g of body weight and 2 g/kg of body weight, respectively) during 5 h. Nonesterified fatty acid (NEFA) and TAG were determined in plasma by enzymatic colorimetric methods according to the manufacturer's instructions (Nanjing Jiancheng Bioengineering).…”
Section: Lipid Tolerance Testmentioning
confidence: 99%